Desafios do executivo aposentado: conflitos e perspectivas - uma leitura junguiana - Mori, Antonio Emilio (2015)
This research aims at getting to know the psychological conflicts faced by retired executives from private companies by identifying solutions developed to face conflicts and providing resources to be used in the development of such solutions. The theory is based on Jungian psychology. The interviews carried out with ten retired executives turned possible to identify the losses, the psychological reactions stemming from those losses, the search for solutions to overcome difficulties, the challenges faced, the resources used and changes in behavior. The loss of the position, power, relationship and social status have led to feelings of void, uselessness, anguish and depression. Work was regarded as vital in the life of those executives and there was evidence of identification with the professional persona. The search for solution involved the use of more developed resources such as thinking, self-reliance and dedication, after a moment of reflection and evaluation of the situation. There was therapeutical help only in more serious cases. Most of executives involved in this research have overcome crisis after a while by rebuilding their persona with the same productive characteristics of the previous persona, returning to the business world and having activities related to their talents and professional experiences. There are emergent cases that preferred the academic field of work as a solution, but still have difficulties in finding meaning to life or in knowing what to do with the knowledge and titles they have. Important behavior changes were observed, among which, more spontaneity, more flexibility, less strictness and more concern about other people. For some interviewees, a previous preparation for retirement has proven to be a way to soften the impact derived from losses, but not for all those who have prepared themselves. To sum up, it is of utmost importance to develop preparation programs that comprise psychological, motivational, conscious and unconscious aspects in order to soften the psychological difficulties faced during transition and help the development of new talents by expanding possibilities of creative solutions